Affärsrelationen - en studie av samspelet mellan drivningsentreprenörer och tjänstemän inom ett virkesområde hos Mellanskog - Johansson, Johnny (2015)
The purpose of this report is to investigate the business relationship between forest machine entrepreneurs and company officials within a timber area at one of the Swedish forest owner associations called Mellanskog. This report shows how these people work with their business relationships, what they believe are the keys getting a successful relationship and how they have got were there they are now. Key words: Business relationship, cooperation, team work, communication, negotiation, respect, commitment and trust.